Nucleoprotein and membrane protein genes are associated with restriction of replication of influenza A/Mallard/NY/78 virus and its reassortants in squirrel monkey respiratory tract. - Tian, S F (1985)
An avian influenza A virus, A/Mallard/NY/6750/78(H2N2), was restricted in in replication in the respiratory tract of squirrel monkeys. Avian-human influenza A reassortant viruses possessing the six RNA segments coding for nonsurface proteins (i.e., internal genes) of this avian virus were as restricted in replication in squirrel monkeys as their avian influenza parent. These findings indicated that restriction of replication of the avian influenza virus is a function of one or more of its internal genes. For an investigation of which of the avian influenza genes was responsible for restricted replication in the respiratory tract of primates, reassortant viruses were produced that contained human influenza virus surface antigens from the A/Udorn/72(H3N2) virus and one or more of the internal genes derived from the avian influenza virus parent. Avian-human reassortant influenza A viruses containing only the nucleoprotein or matrix protein RNA segment from the avian influenza virus parent were as restricted in their growth as an avian-human influenza reassortant virus containing each of the six avian influenza internal genes. In addition, an avian-human influenza reassortant virus possessing only the avian RNA 1 and nonstructural genes (which by themselves do not specify restricted replication) manifested a significant reduction of virus replication in squirrel monkey tracheas. Thus, the avian nucleoprotein and matrix genes appear to play a major role in the host range restriction exhibited by the A/Mallard/78 virus and its reassortants, but the combination of RNA 1 and nonstructural genes also contributes to restriction of replication.